Leptin receptor deficiency impedes metabolic surgery related-weight loss through inhibition of energy expenditure in db/db mice - Dan Tong; Jie Xiang; Wei Liu; Fang Sun; Lijuan Wang; Aidi Mou; Tingbing Cao; Qing Zhou; Mei You; Yingying Liao; Peng Gao; Daoyan Liu; et al. (Diabetology & Metabolic Syndrome, 2024)
Abstract Background Roux-en-Y gastric bypass (RYGB) surgery is an effective metabolic surgery against diabetes and obesity. Clinical evidence indicates that patients with severe obesity have a poor curative effect in losing weight if they suffer from leptin or its receptor deficiency, but the underlying mechanism remains elusive. Here, we investigated the effect of leptin receptor deficiency on metabolic dysfunction in db/db mice treated by RYGB surgery. Methods The db/db mice and their heterozygote control db/m mice were subjected to RYGB or sham surgery. Body weight, blood glucose, food intake and glucose tolerance were evaluated. Micro-PET/CT and histological analysis were performed to examine the glucose uptake of tissues and the fat changes in mice. The key factors in glucose and fatty acid metabolism were detected by western blot analysis. Results Compared with the sham group, the db/db mice in the RYGB group showed more significant weight regain after surgical recovery and improvement in hyperinsulinemia and glucose tolerance. However, the total body fat and multiple organ lipid deposition of RYGB-treated db/db mice was increased. The underlying mechanism studies suggested that the activation of AMPK regulated GLUT4 to increase glucose uptake, but AMPK could not promote fatty acid oxidation through the JAK2/STAT3 pathway under leptin receptor deficiency in db/db mice. Conclusion We conclude that leptin receptor deficiency impedes the AMPK activation-mediated fat catabolism but does not affect AMPK-related glucose utilization after metabolic surgery in db/db mice. This result helps select surgical indications for patients with obesity and diabetes.